Cold war and its origins (1917-1960) - "Fleming, D. F." (London, 1961)
This book is an analysis of the great struggle of the twentieth century, the Cold War. It carefully examines the conflict$1 (Bs origins in the Russian Revolution of 1917, and follows the thread of antagonism between west and east all the way up to 1960. These were the key years of the Cold War, when it seemed that the prospect of nuclear confrontation was a real one, and this book offers a close reading of the main events of those years. s
Keywords: Cold war